Analysis of The Needs for Podcasts As Learning Media for Visually Impaired Students - Setiawati, Reni; Gunarhadi, Gunarhadi; Andayani, Tri Rejeki (Angstrom Centre of Education, 2023)
The formulation of the problem from this research is what is the need for podcasts as a media for learning the visually impaired students? The purpose of this study was to analyze the need for podcasts as learning media for visually impaired students and their benefits for developing podcasts as learning media for visually impaired students. The research method is quantitative and qualitative, namely in the form of a list of tables that are converted into percentages to calculate how many items in a questionnaire to answer a study. While the qualitative is the elaboration of the quantitative data obtained by the researcher. Data collection techniques using questionnaires or questionnaires. The results of the research and discussion data presented can be concluded that the need for podcasts as a learning medium for the blind is indicated by a percentage of 100% meaning that students need learning media that suits their learning style.